(untitled) (Bangladesh Journal of Pharmacology, 2016)
COX-2 expression by means of immunohistochemistry in 120 cases breast invasive ductal carcinomas and 60 cases benign lesions were compared with clinicopathological features and prognostic molecular markers. COX-2 role of invasiveness and chemotaxis in breast cancer cell line MDA-MB-231 by using small RNA interference (siRNA) plasmids to disrupt COX-2 expression in vitro were investigated. The results show that COX-2 immune positivity and percentage of positive cells in breast carcinomas were higher than those in benign lesions and positivity correlated significantly with HIF-1?, VEGF, the grading, metastasis and vascular invasion of carcinoma (p<0.05). This study suggests that COX-2 overexpression correlates with poor clinicopathological parameters in breast cancers, and the reduction of COX-2 expression can obviously inhibit the invasion and chemotaxis of cancer cell line MDA-MB-231 using RNA interference. The findings of the present study suggest that COX-2 overexpression in breast cancer may be considered as a negative prognostic marker.